Using antenna patterns to improve the quality of SeaSonde HF radar surface current maps - Barrick, D.E.; Lipa, B.J. (1999 6th Working Conference on Current Measurement, 1999)
The SeaSonde coastal HF current mapping radar realizes its very small and convenient antenna size by employing the MUSIC direction finding (DF) algorithm, rather than beam forming to determine the bearing angle to each point on the sea plot. Beam forming requires large phased array antennas spanning up to 100 m of linear coastal extent. The SeaSonde uses two colocated crossed loops and an omnidirectional monopole as the receive antenna system. Unique features of DF polar maps can be angle sectors with sparse coverage or gaps. This occurs when the antenna patterns are distorted by nearby terrain or buildings, a frequent effect observed with all HF radars. In addition, uncorrected distortions can produce angle biases (misplacements) of the radial current vectors, sometimes as much as 10/spl deg/. The actual antenna patterns (with distortions) are now measured with a small battery operated transponder, either from land in front of the antenna or from a boat. These are then inserted into the software to calibrate, i.e., correct for the distortions. A number of algorithms have been evaluated for this correction process, both using simulations (with known input) as well as actual measured sea echo. The authors present the latest findings on gap and bias mitigation, which show that nearly all of these deleterious effects can be reduced to acceptable levels.